Acne Basics: Pathophysiology, Assessment, and Standard Treatment Options. (January 2018) - Masterson, Katrina Nice
Abstract : ABSTRACT: Acne is a chronic condition affecting the pilosebaceous unit. Presenting almost daily in the typical dermatology practice, the condition poses numerous treatment challenges due to the complex interaction of its clinical presentation and unique patient needs. The following discussion will provide basic pathophysiology and describe the clinical presentation of acne vulgaris and many of its variants. Several of the standard treatment options will be described. Uncommon variants, acute forms, and more complex treatment regimens will not be discussed here.